Professor Larysa Iukhymivna Cherikchi: a founder of physiotherapy in ophthalmology of Ukraine - N.F. Bobrova; T.M. Serebrina (Journal of Ophthalmology)
Larysa Iukhumivna Cherikchi took her career path into the field recommended by Academician V.P. Filatov, and conducted multi-year versatile experimental and clinical studies for the development of effective physiotherapeutic techniques for the treatment of various eye diseases. She proposed the technique called electroelimination (i.e., electrophoretic elimination of inflammation products from the eye) which (1) expanded opportunities for research on the pathochemistry of ocular inflammatory disease of various etiologies and pathochemistry of low-grade ocular inflammation, and (2) has been successfully used in the treatment of eye disorders. Larysa Iukhumivna brilliantly defended her candidate thesis and doctoral dissertation, which enabled her to achieve the rank of Professor. She was Head of the Ukraine Ministry of Health Research and Methodology Center for Physiotherapy in Ophthalmology. In total, these achievements allow us to state that Larysa Iukhumivna was the founder of academic research into and practical applications of physiotherapy in ophthalmology in Ukraine. The areas in physiotherapy in ophthalmology outlined and initially developed by Larysa Iukhumivna Cherikchi were further developed by her numerous pupils and colleagues at the Filatov Institute.